In Vivo Anchoring Bis‐Pyrene Probe for Molecular Imaging of Early Gastric Cancer by Endoscopic Techniques (Adv. Sci. 4/2023). Issue 4 (3rd February 2023) - Luo, Qiang; Fan, Chaoqiang; Ying, Wang; Peng, Xue; Hu, Yiyang; Luan, Zhaohui; Ye, Shaosong; Gong, Chunli; Huang, Yu; Xiao, Yufeng; Chen, Yang; Xing, Malcolm; et al.
Abstract : Early Gastric Cancer In article number 2203918, Malcolm Xing, Lei Wang, Shiming Yang, and co‐workers constructed a bis‐pyprene (BP) based nanoprobe, which could target and accumulate in angiogenesis of early gastric cancer (EGC), followed by transforming into nanofibers in situ. Most importantly, the probe could visually monitor angiogenesis of EGC by emitting yellow green fluorescence under blue laser endoscopy (BLE), showing great potential for the detection of EGC and guiding surgical resection.